2014
DOI: 10.1111/jdv.12678
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of treatment history and its association with clinical outcomes and relapse in 155 pemphigus patients with response to a single cycle of rituximab

Abstract: Based on these observations, the low-dose rheumatoid arthritis protocol should not be recommended due to the inferior clinical response and shortened time to relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 33 publications
2
37
1
Order By: Relevance
“…In another review, groups treated according to each protocol were found to show similar rates of serious adverse events and mortality . A review conducted by Amber and Hertl found no significant difference in the percentage of patients achieving complete remission between those treated according to the lymphoma versus the RA treatment protocol . However, the lymphoma treatment protocol was identified as superior in terms of risk for relapse in this review .…”
Section: Discussionmentioning
confidence: 52%
“…In another review, groups treated according to each protocol were found to show similar rates of serious adverse events and mortality . A review conducted by Amber and Hertl found no significant difference in the percentage of patients achieving complete remission between those treated according to the lymphoma versus the RA treatment protocol . However, the lymphoma treatment protocol was identified as superior in terms of risk for relapse in this review .…”
Section: Discussionmentioning
confidence: 52%
“…Before its application to pemphigus, rituximab had been approved for non-Hodgkin's lymphoma and rheumatoid arthritis, and both have different protocols. Both the lymphoma and rheumatoid arthritis protocols have been applied to the treatment of pemphigus (Ahmed & Shetty, 2015;Amber & Hertl, 2015;Cho et al, 2014;Kanwar et al, 2014;Kim, Kim, Kim, & Kim, 2011;Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…38 Lower doses of rituximab are less effective 39,40 • Rituximab can be combined with short-term (<4 months old) systemic corticosteroids and long-term (>12 months old) immunosuppressive treatment…”
Section: Immunoadsorptionmentioning
confidence: 99%